SIMULASI KINERJA BATCH AIR BLAST FREEZER DENGAN MENGGUNAKAN SISTEM REFRIGERAN R404A DAN R1234YF - Senu, Stefanus Stef; Dwinanto, Matheus M.; Jafri, Muhamad (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2024)
Performance simulation on air blast freezer batches using two types of refrigerants, namely R404A and R123yf. Air blast freezer is a device used in the food and beverage processing industry to cool products quickly by utilizing cold air generated by convection cooling, modeling and simulation of air blast freezer batch systems using computer modeling software. Important variables considered in the simulation include cooling chamber size, airflow velocity, air distribution, and product geometry characteristics. then performed performance analysis using both refrigerants, R404A and R123yf. The use of R123yf refrigerant as an alternative to R404A can also provide guidance in the selection of more environmentally friendly refrigerants without sacrificing system performance. With improved product efficiency and quality, food and beverage processing industries can optimize refrigeration processes and increase their overall productivity.